Chernobyl record: the definitive history of the Chernobyl catastrophe - Mould, Richard F. (Institute of Physics Publishing, 2011)
The nuclear accident at Chernobyl on April 26, 1986 had a heavy impact on life, health, and the environment. It caused agony to people in the Ukraine, Belarus, and Russia and anxiety far away from these countries. The economic losses and social dislocation were severe in a region already under strain. It is now possible to make more accurate assessments of these effects than it was in the first few years following the catastrophe.